Desinfecção de efluente de reator anaeróbio com pós-tratamento por filtração visando reúso - Matos, Danilo Gabriel dos Santos (My University, 2026)
As a strategy to help mitigate water scarcity, technologies such as double and triple filtration (DF and TF) using sand, activated carbon, and zeolite have been applied in the post-treatment of effluents from UASB reactors to produce high-quality, low-cost reclaimed water. However, the presence of pathogens and the formation of disinfection by-products (DBPs) after filtration still represent significant challenges. In this context, the present study aimed to optimize the coagulation stage to establish optimal conditions across three filtration runs in a pilot-scale triple filtration unit, defining the best coagulation and filtration combinations for subsequent effluent disinfection. The application of chlorine (Cl), peracetic acid (PAA), sodium persulfate (PS), and ozone (O₃), either alone or combined with UV radiation, was evaluated in terms of microbial removal, disinfection by-product (DBP) formation, toxicity, and cost, aiming to assess the feasibility of the final effluent for reuse according to international, national, and state regulations. The results demonstrated that the UASB reactor promoted effluent stabilization, with an average turbidity reduction of 83% and pH around 7.0. Optimized coagulation (100 mg L⁻¹ FeCl₃) associated with filtration achieved turbidity removals of up to 99%, final effluent values below 1 NTU, and removals greater than 90% for COD, BOD, nitrogen, and LAS. The dosage of 100 mg L⁻¹ FeCl₃ provided the best balance between efficiency, effective treated water production, and specific cost. The UASB system combined with coagulation (100 mg L⁻¹ FeCl₃) and triple filtration promoted microbiological reductions of up to 2.95 log, in addition to complete removal of helminth eggs. Disinfection with chlorine, ozone, and peracetic acid achieved complete removal (<LOD) of Escherichia coli and total coliforms, whereas persulfate showed lower performance. Association with UV reduced by 50–70% the disinfectant concentrations required to achieve complete elimination of these indicators. For more resistant microorganisms, UV-combined systems showed superior performance, with complete removal of Clostridium perfringens and enterococci at concentrations of 1.0 to 1.5 mg L⁻¹. Regarding DBPs, only trichloromethane (TCM) was detected, with the highest concentrations associated with chlorine (~11 µg L⁻¹), while UV addition reduced TCM formation by more than 98%. Phytotoxicity assays of disinfected effluents showed low toxic effects, with GI > 58% and RGI > 0.5. Treatment costs ranged from R$ 1.62 to R$ 2.43 m⁻³. The lowest costs were observed for TF/PS and TF/UV/PS, while the highest corresponded to TF/O₃ and TF/UV/O₃. Finally, the TF/Cl, TF/PAA, TF/O₃ treatments and their UV-combined systems complied with the main agricultural, urban, and industrial water reuse standards across different continents.
Keywords: reúso de efluente; dupla e tripla filtração; desinfecção; custo-benefício; sustentabilidade; Effluent reuse; double and triple filtration; disinfection; cost–benefit; sustainability